2002
DOI: 10.1086/340126
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus fermentumRC‐14 InhibitsStaphylococcus aureusInfection of Surgical Implants in Rats

Abstract: Staphylococcus aureus is a common cause of community and hospital-acquired infections. Moreover, the clinical impact of S. aureus is on the rise because of the global increase in the incidence of multidrug-resistant strains and its growing prevalence as a major cause of surgical infections. As a result, there is a pressing need to identify new antistaphylococcal agents and preventative strategies that will help in the management of these types of infections. This report describes the successful use of a probio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(95 citation statements)
references
References 15 publications
1
93
0
1
Order By: Relevance
“…Our results raise intriguing questions about the usefulness of probiotics, including LGG, in the context of infection. Indeed, Gan et al (45) reported that Lactobacillus fermentum RC-14 and its secreted biosurfactant inhibit S. aureus infection and bacterial adherence to surgical implants.…”
Section: Discussionmentioning
confidence: 99%
“…Our results raise intriguing questions about the usefulness of probiotics, including LGG, in the context of infection. Indeed, Gan et al (45) reported that Lactobacillus fermentum RC-14 and its secreted biosurfactant inhibit S. aureus infection and bacterial adherence to surgical implants.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, other versions of microbial antagonisms, which do not directly kill pathogens, have also been investigated. One interesting example is that Lactobacillus fermentum RC-14, a probiotic bacterial isolate, inhibited acute Staphylococcus aureus infection (19). The probiotic bacteria did not appear to affect pathogen growth: rather, the pathogen secretes cell surface extracellular matrix-binding proteins and biosurfactant that somehow prevented pathogen adherence to surgical implants and inhibited S. aureus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the application of viable lactic acid bacteria to an infected wound would represent a paradigm shift in current surgical practice. In a series of animal studies, L. fermentum RC-14 and proteins produced by this organisms were shown to prevent severe Staphyoloccus aureus surgical implant infection (40). Although this does not prove human efficacy, the concept illustrates a different approach to wound infection management.…”
Section: Probiotics For Surgical Infectionsmentioning
confidence: 99%